DINAMIKA KEPENDUDUKAN DAN HUBUNGANNYA TERHADAP PENYEDIAAN SARANA DAN PRASARANA PENDIDIKAN DAN KESEHATAN SERTAPENINGKATAN IPM DI KABUPATENKAYONG UTARA - B01112070, Sabariah (Jurnal Curvanomic, 2016)
AbstractÂ  This study aimed to analyze the relationship of population growth on the provision of educational facilities and health as well as an increase in the HDI in the district of North Kayong. This study uses descriptive analysis and qualitative approaches. The results of this study show the relationship of the dynamics of the population in the District of North Kayong in 2010-2014 on the provision of facilities and infrastructure in the areas of education and health as well as an increase in the HDI in the district of North Kayong. The population of the District of North Kayong increases starting from the 2010-2014, but the population growth rate has decreased in line with the increase in the provision of facilities and infrastructure in the areas of education and health as well as increasing IPM. In line with this increase, the education budget from the budget of the District of North Kayong commencing in 2010-2014 remained at 20%, while health spending has fluctuated. Keywords: Population Growth Rate, Education, Health, HDI